Animal and Cell Culture Models of PPGLs – Achievements and Limitations - Karna, Bhargavi; Pellegata, Natalia Simona; Mohr, Hermine (Hormone and Metabolic Research, 2024)
Research on rare tumors heavily relies on suitable models for basic and translational research. Paragangliomas (PPGL) are rare neuroendocrine tumors (NET), developing from adrenal (pheochromocytoma, PCC) or extra-adrenal (PGL) chromaffin cells, with an annual incidence of 2–8 cases per million. While most PPGL cases exhibit slow growth and are primarily treated with surgery, limited systemic treatment options are available for unresectable or metastatic tumors. Scarcity of appropriate models has hindered PPGL research, preventing the translation of omics knowledge into drug and therapy development. Human PPGL cell lines are not available, and few animal models accurately replicate the disease’s genetic and phenotypic characteristics. This review provides an overview of laboratory models for PPGLs, spanning cellular, tissue, organ, and organism levels. We discuss their features, advantages, and potential contributions to diagnostics and therapeutics. Interestingly, it appears that in the PPGL field, disease models already successfully implemented in other cancers have not been fully explored.
Keywords: pheochromocytoma; paraganglioma; PDX; SDHx; neuroendocrine tumor